Survey of outpatient sputum cytology: influence of written instructions on sample quality and who benefits from investigation. Issue 1 (March 1992) - Tsang, K W; Bentley, A M; Mann, J S; Belcher, J; Pantin, C F
Abstract : OBJECTIVES--To evaluated quality of outpatient sputum cytology and whether written instructions to patients improve sample quality and to identify variables that predict satisfactory samples. DESIGN--Prospective randomised study. SETTING--Outpatient department of a district general hospital. PATIENTS--224 patients recruited over 18 months whenever their clinicians requested sputum cytology, randomized to receive oral or oral and written advice. INTERVENTIONS--Oral advice from nurse on producing a sputum sample (114 patients); oral advice plus written instructions (110). MAIN MEASURES--Percentages of satisfactory sputum samples and of patients who produced more than one satisfactory sample; clinical or radiological features identified from subsequent review of patients' notes and radiographs associated with satisfactory samples; final diagnosis of bronchial cancer. RESULTS--588 sputum samples were requested and 477 received. Patients in the group receiving additional written instructions produced 75(34%) satisfactory samples and 43(39%) of them one or more sets of satisfactory samples. Corresponding figures for the group receiving only oral advice (80(31%) and 46(40%) respectively)were not significantly different. Logistic regression showed that radiological evidence of collapse or consolidation (p<0.01) and hilar mass (p<0.05) were significant predictors of the production of satisfactory samples. Sputum cytology confirmed the diagnosis in only 9(17%) patients with bronchial carcinoma. CONCLUSIONS--The quality of outpatients' sputum samples was poor and was not improved by written instructions. Sputum cytology should be limited to patients with probable bronchial cancer unsuitable for surgery. IMPLICATIONS--Collection of samples and requests for sputum cytology should be reviewed in other hospitals.